2009
DOI: 10.1093/ntr/ntp053
|View full text |Cite
|
Sign up to set email alerts
|

The association of depressive, anxiety, and stress symptoms and postpartum relapse to smoking: A longitudinal study

Abstract: Discussion : Among women who quit smoking during pregnancy, a worsening of depressive and stress symptoms over 12 weeks postpartum was associated with an increased risk of smoking by 24 weeks. IntroductionApproximately one third of female smokers quit once they learn that they are pregnant ( Fingerhut, Kleinman, & Kendrick, 1990 ;Floyd, Rimer, Giovino, Mullen, & Sullivan, 1993 ;LeClere & Wilson, 1997 ;Severson, Andrews, Lichtenstein, Wall, & Zoref, 1995 ), but up to two thirds of women who stop smoking during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 31 publications
3
77
2
4
Order By: Relevance
“…The high rates of relapse following delivery in this study are consistent with the smoking literature (Gyllstrom et al, 2012;Park et al, 2009;Tran et al, 2013;Yasuda et al, 2013) and the limited literature on postpartum relapse to alcohol and illicit substances (Ebrahim and Gfroerer, 2003;Gilchrist et al, 1996;Howell et al, 1999). However, the longitudinal nature of this study is unique and allows us to estimate the reduction of substance use over the course of pregnancy and the pattern of relapse in the first two years following delivery.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high rates of relapse following delivery in this study are consistent with the smoking literature (Gyllstrom et al, 2012;Park et al, 2009;Tran et al, 2013;Yasuda et al, 2013) and the limited literature on postpartum relapse to alcohol and illicit substances (Ebrahim and Gfroerer, 2003;Gilchrist et al, 1996;Howell et al, 1999). However, the longitudinal nature of this study is unique and allows us to estimate the reduction of substance use over the course of pregnancy and the pattern of relapse in the first two years following delivery.…”
Section: Discussionsupporting
confidence: 84%
“…The majority of research has focused on smoking relapse postpartum (Colman and Joyce, 2003;Gyllstrom et al, 2012;Kaneko et al, 2008;Park et al, 2009;Ruger et al, 2008;Tong et al, 2008;Tran et al, 2013;Yasuda et al, 2013), with only a handful of studies looking at postpartum alcohol relapse (Ebrahim et al, 1998;Fleming, 2007a, 2007b;Nayak and Kaskutas, 2004). One of these studies found that at six to 12 weeks postpartum 37.8% of women who were frequent drinkers before pregnancy reported postpartum risky drinking, with 18% reporting heavy episodic drinking, 5% frequent drinking only and 15% reporting both behaviors (Jagodzinski and Fleming, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, women who reported smoking during pregnancy were more likely to report PPD symptomatology than their non-smoking counterparts [50,55,56]. Smoking during pregnancy has been previously established as associated with being multiparous, pregnancy unwantedness and current or previous diagnoses of depression [57]. In a recent study, smoking relapse 24 weeks postpartum was attributed to negative emotions [57], however the relationship between antenatal sedentary behavior and smoking on PPD is understudied and remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment efficacy among low-income pregnant/postpartum women might be further enhanced by addressing the myriad of stressors common among such populations, including high levels of stress, negative affect and depression, and low levels of social support (Allen, Prince, & Dietz, 2009;Park et al, 2009;Reitzel et al, 2007). These, and other stressors (e.g., partner relational problems, financial difficulty), often derail women's attempts to maintain smoking abstinence (Ripley-Moffitt et al, 2008) and clearly warrant attention within a broader based treatment program.…”
Section: Introductionmentioning
confidence: 99%